ACCOUNTING AND ANALYTICAL IMPLEMENTATION OF ENTERPRISE’S CASH FLOW MANAGEMENT - Шубіна, Світлана; Піскунов, Роман; Любимова, Світлана (Socio-economic relations in the digital society, 2019)
Theoretical and methodical approaches of accounting and analytical implementation of enterprise’s cash flow management were investigated and colligated at the article. The definition of the concept of «cash flows» from different sources were analyzed. Own definition of cash flow was suggested. Essence and principles of cash flow management were investigated: systemicity, complexity, dynamism, integrability, alternative, optimality, scientific substantiation. The stages of management of cash fl ows of the enterprise are described: accounting of cash flows and formation of reporting, analysis, planning of cash fl ows in terms of types of activity, optimization of cash flows and control process. The importance of step-by-step cash fl ow management process implementation for the enterprise is determined, which ensures an increase in the effi ciency of cash flow distribution in the enterprise, ensuring constant control over the movement of cash and achieving financial equilibrium.